2017
DOI: 10.1159/000478030
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Two Different Initial Dosing Regimens of Intravitreal Ranibizumab Used to Treat Myopic Choroidal Neovascularization

Abstract: Purpose: To compare two different initial dosing regimens of intravitreal ranibizumab used to treat myopic choroidal neovascularization. Methods: A total of 61 eyes of 56 patients were treated: 26 eyes received a single injection followed by treatment pro re nata (1+ PRN), while 35 eyes first received 3 consecutive monthly injections (3+ PRN). Results: The mean follow-up was 53 ± 16 months. The visual acuities were 51.9 ± 16.2 letters with 3+ PRN and 53 ± 22.4 letters with 1+ PRN at baseline (p = 0.824); 69.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The 47% of patients did not require a re-injection till the end of the followup period. The results of many studies indicated that there is no significant difference between the two treatment schemes in terms of improved vision [24] . However, some scholars believe that the 3+PRN regimen can make the initial treatment reach the loading dose, which may reduce the recurrence rate or delay the CNV recurrence [25] .…”
Section: Conbercept In the Treatment Of Choroidal Neovascularizationmentioning
confidence: 99%
“…The 47% of patients did not require a re-injection till the end of the followup period. The results of many studies indicated that there is no significant difference between the two treatment schemes in terms of improved vision [24] . However, some scholars believe that the 3+PRN regimen can make the initial treatment reach the loading dose, which may reduce the recurrence rate or delay the CNV recurrence [25] .…”
Section: Conbercept In the Treatment Of Choroidal Neovascularizationmentioning
confidence: 99%